DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN PSYCHOLOGY: THEORETICAL FOUNDATIONS, APPLIED ASPECTS, AND ETHICAL CHALLENGES (Uzbekistan Open Conference, 2026)
The article examines contemporary directions of integrating digital technologies and artificial intelligence systems into psychological science and practice. The theoretical and methodological foundations of the digital transformation of psychology are analyzed, along with the application of machine learning algorithms in psychological assessment, psychotherapy, and empirical research. Particular attention is paid to the validity and reliability of digital tools, issues of algorithmic bias, data privacy, and professional responsibility. The paper substantiates the necessity of developing interdisciplinary standards, ethical regulations, and legal frameworks governing digital psychological practice. It is concluded that artificial intelligence should be viewed not as a replacement for the psychologist, but as a tool that enhances professional capabilities while preserving the humanistic principles of the discipline.